A General Approach to Discrete-Time Adaptive Control Systems with Perturbed Measures for Complex Dynamics - Case Study: Unmanned Underwater Vehicles - Jordán, Mario Alberto; Bustamante, Jorge Luis (IntechOpen, 2011)
None